2008
DOI: 10.1111/j.1751-7893.2008.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of the literature regarding early intervention for children and adolescents aged 0–15 experiencing a first‐episode psychiatric disturbance

Abstract: The authors highlight information that has the potential to assist in optimizing care for those youth younger than 16 years experiencing or exhibiting signs of a first-episode psychiatric disturbance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 102 publications
(415 reference statements)
0
10
0
Order By: Relevance
“…Insufficient age‐appropriate mental health services deter youth with significant mental health problems from obtaining suitable help (Cosgrave et al. 2008, Leavey et al. 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient age‐appropriate mental health services deter youth with significant mental health problems from obtaining suitable help (Cosgrave et al. 2008, Leavey et al. 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Mental health problems are common among young people and their effects are significant. According to one study, 20% of youth under the age of 16 have a diagnosable mental health disorder (Leavey, Flexhaug, & Ehmann, 2008), while another study found rates as high as 40% (Copeland, Shanahan, Costello, & Angold, 2011). Some studies have shown that nearly half of all mental disorders onset in childhood (Copeland, et al, 2011).…”
Section: Adolescent Mental Health Problemsmentioning
confidence: 99%
“…Unfortunately, only one in six of those who would benefit from treatment ever receive it. (Leavey, et al, 2008).…”
Section: Adolescent Mental Health Problemsmentioning
confidence: 99%
“…Additionally, research reveals that age fifteen is the average age for long-term mental health illnesses (such as schizophrenia or bipolar disorder) to occur (Ehmann et al, 2014;Leavey et al, 2008). Bhui et al, (2014)'s research shows specifically that "patients presenting with psychotic disorders are usually young at first episode" (p. 1).…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…Other proposals for directing research towards supporting families (such as grief counseling) have been proposed to help families remain healthy under stressful circumstances to continue help-seeking for non-healthy family members (Leavey et al, 2008) and should be further researched as well.…”
Section: Familiesmentioning
confidence: 99%